MRI-Fusion Targeted vs. Systematic Prostate Biopsy–How Does the Biopsy Technique Affect Gleason Grade Concordance and Upgrading After Radical Prostatectomy? - Rührup, Jessica; Preisser, Felix; Theißen, Lena; Wenzel, Mike; Roos, Frederik C.; Becker, Andreas; Kluth, Luis A.; Bodelle, Boris; Köllermann, Jens; Chun, Felix K. H.; Mandel, Philipp (Frontiers in Surgery, 2019)
Introduction: MRI-targeted biopsy (TB) increases overall prostate-cancer (PCa) detection-rates and decreases the risk of insignificant PCa detection. However, the impact of these findings on the definite pathology after radical prostatectomy (RP) is under debate. Materials and Methods: Between 01/2014 and 12/2018, 366 patients undergoing prostate biopsy and RP were retrospectively analyzed. The correlation between biopsy Gleason-score (highest Gleason-score in a core) and the RP Gleason-score in patients undergoing systematic biopsy (SB-group) (n = 221) or TB+SB (TB-group, n = 145) was tested using the ISUP Gleason-group grading (GGG, scale 1–5). Sub analyses focused on biopsy GGG 1 and GGG ≥ 2. Results: Proportions of biopsy GGG 1–5 in the SB-group and TB-group were 24.4, 37.6, 19, 10.9, 8.1% and 13.8, 43.4, 24.2, 13.8, 4.8%, respectively (p = 0.07). Biopsy and pathologic GGG were concordant in 108 of 221 (48.9%) in SB- and 74 of 145 (51.1%) in TB-group (p = 0.8). Gleason upgrading was recorded in 33.5 and 31.7% in SB- vs. TB-group (p = 0.8). Patients with biopsy GGG 1 undergoing RP showed an upgrading in 68.5%(37/54) in SB- and 75%(15/20) in TB-group (p = 0.8). In patients with biopsy GGG ≥ 2 concordance increased for both biopsy approaches (54.5 vs. 55.2% for SB- vs. TB-group, p = 0.9). Discussion: Irrespective of differences in PCa detection-rates between TB- and SB-groups, no significant differences in GGG concordance and upgrading between patients of both groups undergoing biopsy, followed by RP, were recorded. Concordance rates increased in men with biopsy GGG ≥ 2. TB seems to detect more patients with PCa without a difference in concordance with final pathology.